IMPLEMENTASI METODE WEIGHTED PRODUCT PADA SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN PENJURUSAN DI SEKOLAH MENENGAH ATAS ( Studi Kasus di SMA Negeri 1 Lebakwangi ) - Erlan Darmawan; Feri Friatna (NUANSA INFORMATIKA, 2011)
Student majors at senior high school will be done by teacher when the student class move from first grade to second grade . Student majors will effect the student himself if the student wants study from senior high school to the university. The problem that often occurs in the student majors is the use of manual systems to decide the placement of students’ majors. So in the end of studenst’ majors process, teacher is in a rush with time to complete the process of placement of student majors.  If the process isn’t done carefully, it will have technical failure or invalid information. The amount of first grade students also effect the processes of placement of the student majors. The Weight Product method is used to link attributes rating where each attribute rating must be raised first with the weight of the relevant attributes. Development of web decision support systems student majors use weighted product method that can facilitate the counseling teacher at the school to process student data and calculations to decide the students’ majors. That method also can make time efficient. We can get information more quickly and the system provides alternate recommendation to decide student majors well and reference based on the students’ ability.Keywords:Decision Support Systems, Weighted Product Methods, Students Majors